Influence of inulin addition on physical properties and sensory of `Dadih`. - Ishak, Ruzaina; Mustafa, Shuhaimi; Sipat, Abdullah; Syed Muhammad, Sharifah Kharidah; Abd. Manap, Mohd. Yazid (Asian Network for Scientific Information, 2006)
The aim of this study was to evaluate the physical and organoleptic properties of 'dadih' supplemented with inulin among students and staffs in University Putra Malaysia during the year 2004. Supplementation of inulin was shown to increase hardness, fracturability and cohesiveness but decrease syneresis of the resulting 'dadih'. In addition, sensory evaluation showed that trained panelist judged 'dadih' made from skim milk and fresh milk as acceptable. The whole study indicates that inulin can be used as additives in 'dadih' making in order to improve the physical properties and sensory of 'dadih' product. © 2006 Asian Network for Scientific Information.